Peningkatkan Penguasaan Kosakata Bahasa Inggris Melalui Metode VCD Pada Siswa Kelas II di SDN Rorotan 03 Pagi Kelurahan Rorotan Cilincing Jakarta Utara - Ika Yulistiana (LP3M Universitas Islam Zainul Hasan Genggong, 2019)
The purpose of this study was to improve the mastery of English vocabulary through the VCD media method on class II students in SD N Rorotan 03 Morning Village in Rorotan Sub-District, Cilincing District, North Jakarta. This research was conducted on 32 year old children. This study was an action research with Kemmis and Taggart models consisting of 4 stages namely (plan, action, observation and reflection). This study consisted of 2 cycles, with each cycle as many as four meetings. Data collection techniques are using observation, field notes, and documentation. Data analysis uses quantitative and qualitative. Quantitative data analysis is carried out with statistical descriptions to compare pre cycles to the second cycle. The stages of qualitative analysis are data reduction, display data and verification. The results showed that there was an increase in English vocabulary mastery through the VCD media method. Theresults of the study quantitatively addressed the learning outcomes of vocabulary improvement in 32 children with an average of 58. 53% so that the results had not reached KKM, then continued in the first cycle to experience the average vocabulary ability is 71. 31% and then in cycle II the average vocabulary is 84.06%. Keywords: Mastery of vocabulary English words and VCD methods